Prototipe Powered Emergency Resuscitator Berbasis Bag Valve Mask - Ghandy, Ghandy; Panggabean, Jayandi; Lalujan, Virginia; Naulid, Maria Anindita; Lawalata, Sanga (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The COVID-19 pandemic proves that healthcare capacity and equipment are not sufficient to handle a pandemic, especially the availability of ventilators. Composed of more than 17.500 islands, 6.000 of which are inhabited, Indonesia’s demographic varies widely from one area to another. Health infrastructure in many areas is minimal, with many having no hospitals but clinics with limited resources/funds and minimally-trained healthcare professionals. The need for domestically produced ventilators is clear. But not only that, there is a need to produce simpler/more economical ventilators that are affordable and simpler to operate. This paper will discuss the basic ventilator (resuscitator), built upon MIT Open Design (used by clinics/smaller hospitals) and was in the last development phase before product testing at Balai Pengamanan Fasilitas Kesehatan (BPFK) Jakarta.